(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the role of Russian poetry experience in the formation of E. Vakhidov’s poetic thinking. The study analyzes the creative assimilation of artistic and aesthetic principles of the Russian poetic tradition and their reflection in the individual poetics of the Uzbek poet. Special attention is paid to the distinction and scholarly interpretation of the concepts “culture of speech” and “culture of language,” as well as “culture of speech” and “speech correctness.” It is emphasized that the culture of language is associated with the system and norms of the literary language, whereas the culture of speech reflects the conscious, purposeful, and aesthetically justified use of linguistic means in a particular communicative context. Speech correctness is considered a necessary but not exhaustive component of the culture of speech. The article concludes that E. Vakhidov’s engagement with Russian poetic experience contributed to the deepening of his poetic thinking, the expansion of expressive linguistic possibilities, and the formation of a high culture of poetic speech.